2016
DOI: 10.15446/rcp.v25n1.44558
|View full text |Cite
|
Sign up to set email alerts
|

Resiliencia y Variables Asociadas en Cuidadores Informales de Pacientes con Alzheimer

Abstract: <p>La resiliencia es una variable protectora ante el rol del cuidador, por ello, este estudio pretende identificar la relación entre la resiliencia y la sobrecarga, la depresión, la percepción de apoyo social y estrategias de afrontamiento. Se trata de un estudio transversal de alcance correlacional que contó con una muestra de 101 cuidadores, evaluados por medio de los instrumentos Zarit, MOS, IDER, Coping, la Escala de Resiliencia de Wagnild y Young. Se identificaron correlaciones positivas estadística… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
2
7
0
2
Order By: Relevance
“…Social support is another relevant protective factor which has also occasionally been studied as a form of coping strategy. Different studies have noted that positive communication between family members and relatives encourages resilience in the family context, fosters a social network of trust and security, and increases caregiver self-efficacy (Cerquera & Pabón, 2016;Palacio et al, 2019). In line with this, our study has shown that the principal coping strategies that correlate with resilience are problem-solving and social support.…”
Section: Discussionsupporting
confidence: 87%
“…Social support is another relevant protective factor which has also occasionally been studied as a form of coping strategy. Different studies have noted that positive communication between family members and relatives encourages resilience in the family context, fosters a social network of trust and security, and increases caregiver self-efficacy (Cerquera & Pabón, 2016;Palacio et al, 2019). In line with this, our study has shown that the principal coping strategies that correlate with resilience are problem-solving and social support.…”
Section: Discussionsupporting
confidence: 87%
“…It is associated with developing skills such as control over memories of a traumatic situation, integrating memory and emotion, regulating trauma-related emotions, controlling symptoms, self-esteem, internal cohesion, establishing safety signs, understanding the impact of trauma, and achieving a positive meaning (18). Likewise, resilience positively affects physical health, improves survival and mental health, and significantly reduces the risk of developing depression, anxiety, and stress (19).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [33,41,46,52,53] agree about the positive correlation between resilience and fewer mental (depression) and physical health problems, as well as a lower risk of institutionalization of the patient. High levels of resilience appear to be related to personal growth [31], with the implementation of skills and competencies of work commitment [49,52,54,55], as well as with a greater capacity for self-care [41,52] and the more benign perception of aspects derived from care [47].…”
Section: Discussionmentioning
confidence: 99%